Peran adat istiadat dalam terbentuknya solidaritas sosial Suku Togutil di Kecamatan Maba Utara Kabupaten Halmahera Timur - Lolo, Arnel Marthen; Pati, Agustinus B; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
Indigenous peoples Togutil tribe in East Halmahera, categorized primitive tribes but why can soidaritas well maintained compared to modern society in identical scientific community. This study used a qualitative descriptive method. This study aims to describe and understand the behavior patterns of public interest as it is in the context Togutil intact so as to describe the properties Togutil public interest in life activities. Based on the research results can be concluded that the customs of the strong role that social solidarity terbentiknya Togutil in the District of North Maba. For Togutil tribe who remained in the forest or in the three villages namely in Forest Tribe Togutil is keeping customs, strong solidarity with others around the settlement. So the authors suggest Togutil tribal communities in the District of North Freshmen need to keep the preservation of culture / customs and leave the lifestyle that can not accept social change. One of the negative impact is not open to other tribes so Communities for Parts Togutil always glued to the natural life. Keywords: customs, social solidarity, community